Clinical, radiological and patient-rated outcome comparison between total and partial ulnar head implants. (March 2022) - Estermann, Lea; Reissner, Lisa; Rosskopf, Andrea B.; Schweizer, Andreas; Nagy, Ladislav
This study aimed to analyse the clinical and radiological outcomes after ulnar head replacement and to compare partial and total ulnar head implants. Twenty-two patients with 23 implants were available with a mean follow-up time of 7 years (range 1.3 to 17) after distal radioulnar joint arthroplasty. At the final follow-up, patients had a low level of pain at rest and during effort, a median Disabilities of the Arm, Shoulder, and Hand (DASH) score of 12 and Patient-Rated Wrist Evaluation score of 12 with partial ulnar head implants, and scores of 20 and 22 in total ulnar head implants, respectively. While the range of motion in patients with partial ulnar head implants was slightly reduced in comparison with the preoperative condition and to the patients with total ulnar head implants, there was a tendency to a higher grip strength and rotational torque. Both types of prosthesis showed sigmoid notch resorptions and resorptions around the neck. We conclude that the results after partial ulnar head replacement do not significantly differ from the total ulnar head implants in many aspects. Level of evidence: III